ANALYSIS OF THE PERSONNEL’S CONSISTENT READINESS FOR CHANGES AS ILLUSTRATED BY THE EXAMPLE OF AN EXPORT-ORIENTED BIOTECHNOLOGICAL ENTERPRISE - E. V. Kazakova; V. P. Trukhin; I. A. Narkevich; I. I. Basakina (Фармация и фармакология (Пятигорск))
The biotechnology industry is currently one of the most dynamically developing sectors of the pharmaceutical industry, that is why it requires improvement in the personnel management system aimed at increasing the flexibility and adaptability of the organization.The aim of the research is to determine the degree of readiness of the organization’s employees for innovations as illustrated by the example of an export-oriented enterprise.Materials and methods. The source information was collected from the employees of the biotechnological enterprise through a questionnaire survey. The representative sample included 588 respondents. The statistical processing of data was carried out using the specialized software IBM SPSS STATISTICS (IBM, USA, 2017). The consistent readiness of the organization’s employees for innovations was determined using I.O. Zagashev’s methods. To assess the reliability of the psychological test, an internal consistency model with Cronbach’s alpha was applied. Statistical hypotheses were tested by comparing the central tendencies of two independent samples using Student’s t-test and the Mann–Whitney nonparametric test.Results. The distribution results of key motivating factors for personnel showed that motivating factors such as an adequate salary and sustainable employment took the leading positions. However, the assessment of the employees’ consistent readiness for innovations according to I.O. Zagashev’s methods shows a high degree of the personnel’s readiness for changes due to positive emotional perception of any innovations.Conclusion. The results obtained make it possible to arrive at the conclusion that the established team favorably responds to all innovations, and is ready to support them in the future being aware of the organization’s desire for innovations. In the future, the results will be used to determine the required management functions and goals and to develop the personnel management strategy in the context of the knowledge transfer, technology and export policy of the pharmaceutical enterprise.